Six Sigma and SWOT Integration for Donut Quality Control: Integrasi Six Sigma dan SWOT untuk Pengendalian Kualitas Donat - Purvandala , Muhammad Kiki; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Quality control is a critical element in manufacturing systems, including food-based Micro, Small, and Medium Enterprises, to ensure customer satisfaction and process consistency. Specific Background: UD Darjo’s Donut’s experienced product defects exceeding the internal standard of 4%, affecting production efficiency and sales performance. Knowledge Gap: Limited structured integration of Six Sigma measurement and SWOT strategic formulation has been applied in small-scale food enterprises to simultaneously evaluate process capability and strategic positioning. Aims: This study aims to determine the sigma level of donut production using the Six Sigma DMAIC approach and to formulate improvement strategies through SWOT analysis. Results: The findings reveal five critical defects, namely undercooked dough, burnt surface, inconsistent shape, wrinkled texture, and hollow structure. The highest sigma value was 4.00 in the first period, the lowest was 3.64 in the fifth period, with an average sigma level of 3.78. SWOT analysis positioned the enterprise in Quadrant I, indicating strong internal capabilities and promising market opportunities. Novelty: This research integrates quantitative sigma measurement with strategic quadrant mapping in a food MSME context. Implications: The study provides structured quality monitoring and strategic marketing expansion recommendations to support continuous product consistency and business sustainability. Keywords: Six Sigma, Quality Control, SWOT Analysis, Food MSMEs, DMAIC Key Findings Highlights Five critical defect categories were identified through process mapping and fishbone analysis. Production capability averaged 3.78 sigma across six months of observation. Strategic positioning indicates aggressive market expansion through strength–opportunity alignment.